Metabolism of acetylcholine in the nervous system of Aplysia californica. I. Source of choline and its uptake by intact nervous tissue (The Rockefeller University Press, 1975)
Although acetylcholine is a major neurotransmitter in Aplysia, labeling studies with methionine and serine showed that little choline was synthesized by nervous tissue and indicated that the choline required for the synthesis of acetylcholine must be derived exogenously. Aanglia in the central nervous system (abdominal, cerebral, and pleuropedals) all took up about 0.5 nmol of choline per hour at 9 muM, the concentration of choline we found in hemolymph. This rate was more than two orders of magnitude greater than that of synthesis from the labeled precursors. Ganglia accumulated choline by a process which has two kinetic components, one with a Michaelis constant between 2-8 muM. The other component was not saturated at 420 muM. Presumably the process with the high affinity functions to supply choline for synthesis of transmitter, since the efficiency of conversion to acetylcholine was maximal in the range of external concentrations found in hemolymph.